2022
DOI: 10.21608/aijpms.2022.131769.1123
|View full text |Cite
|
Sign up to set email alerts
|

Potential Anti-fungal Activity of Lactobacilli Probiotic Against Fluconazole Resistant Candida albicans Clinical Isolates

Abstract: Fluconazole resistance by Candida albicans (C. albicans) is a growing medical issue which makes patient management more difficult. The development of new effective, safe and inexpensive alternatives becomes essential. Probiotics represent an intriguing strategy that can be applied for prevention or treatment of Candida infections. The aim of our study is to investigate the anti-fungal activity of different Lactobacillus species against fluconazole resistant C. albicans isolates and to evaluate the inhibitory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Several studies have shown that Lactobacillus rhamnosus , Lactobacillus reuteri , and Lactobacillus salivarius ( L. salivarius ) possess potent antifungal activity against C. albicans infection ( De Gregorio et al., 2019 ; Vazquez-Munoz and Dongari-Bagtzoglou, 2021 ; El-Ashmony et al., 2023 ). Supernatants of L. salivarius demonstrate antifungal effects against Candida spp., with lactic acid accumulation in the medium ( Zangl et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that Lactobacillus rhamnosus , Lactobacillus reuteri , and Lactobacillus salivarius ( L. salivarius ) possess potent antifungal activity against C. albicans infection ( De Gregorio et al., 2019 ; Vazquez-Munoz and Dongari-Bagtzoglou, 2021 ; El-Ashmony et al., 2023 ). Supernatants of L. salivarius demonstrate antifungal effects against Candida spp., with lactic acid accumulation in the medium ( Zangl et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%